2017
DOI: 10.1038/srep40165
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of catalysis by type-II NADH:quinone oxidoreductases

Abstract: Type II NADH:quinone oxidoreductase (NDH-2) is central to the respiratory chains of many organisms. It is not present in mammals so may be exploited as an antimicrobial drug target or used as a substitute for dysfunctional respiratory complex I in neuromuscular disorders. NDH-2 is a single-subunit monotopic membrane protein with just a flavin cofactor, yet no consensus exists on its mechanism. Here, we use steady-state and pre-steady-state kinetics combined with mutagenesis and structural studies to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 41 publications
(74 reference statements)
10
83
0
Order By: Relevance
“…Currently, some of the described FAD/NADH-dependent oxidoreductases are considered in microbiology a crucial target of antibiotics or chemotherapeutics (i.e., those structurally related to RYL-552, a quinolinic derivative or to SL827, a sulphonamide derivative [10,48,[51][52][53]) because those enzymes play a fundamental role for the ATP synthesis and oxidative pathways in most microorganisms. The lack of NDH-2-orthologous enzymes in Mammalia was retained an important proof of the selective action of potential drug development [10,[54][55][56][57].…”
Section: 2mentioning
confidence: 99%
“…Currently, some of the described FAD/NADH-dependent oxidoreductases are considered in microbiology a crucial target of antibiotics or chemotherapeutics (i.e., those structurally related to RYL-552, a quinolinic derivative or to SL827, a sulphonamide derivative [10,48,[51][52][53]) because those enzymes play a fundamental role for the ATP synthesis and oxidative pathways in most microorganisms. The lack of NDH-2-orthologous enzymes in Mammalia was retained an important proof of the selective action of potential drug development [10,[54][55][56][57].…”
Section: 2mentioning
confidence: 99%
“…Low iron also resulted in a 1.7 LFC of PA2691 ( Supplementary Dataset S1 ), which is a predicted type II NADH:quinone oxidoreductase (NDH-2). NDH-2 proteins utilize flavin cofactors instead of iron to catalyze the oxidation of NADH and reduce quinones (39). Thus, PA2691 may function in place of the nuoA-N encoded complex I to oxidize NADH under low iron conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that cyoA expression increases under low iron conditions via loss of Fur repression (31), most likely due to requiring less iron than the other four oxidases. Under iron-replete conditions, the NADH dehydrogenase I, comprised of NuoA-N, is the predominant NADH dehydrogenase as it not only recycles NADH to NAD + but also helps to generate a proton motive force that can be used to generate ATP (39). Likewise, the cbb 3 -type cytochrome oxidases are the predominant terminal oxidases, as they interact with the cytochrome bc 1 complex, which also contributes to the proton motive force (63).…”
Section: Discussionmentioning
confidence: 99%
“…S8) showed a decrease in flavin absorbance at 456 nm and an increase in absorption in the 500 -700 nm region. The decrease of flavin absorption is caused by electron transfer from NADH to the oxidized flavin moiety, whereas formation of the species that absorbs at long wavelengths is caused by formation of a charge-transfer complex (HadX FADHϪ -NAD ϩ ) similar to what has been observed dur-ing the reductive half-reactions of many flavin reductases (21,31,35,43). When similar experiments using NADPH were carried out, we could not detect any reduction of the enzyme-bound flavin by NADPH within 30 s (data not shown), indicating that HadX is only specific for using NADH as a reductant.…”
Section: Kinetics Of Flavin Reduction On Hadxmentioning
confidence: 94%